2006
DOI: 10.1111/j.1472-765x.2006.02023.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new chromogenic agar medium for isolation and identification of Group B streptococci

Abstract: Aims:  To evaluate a new chromogenic agar as a screening medium for the isolation of Group B streptococci from high vaginal swabs from pregnant women. Methods and Results:  The medium was evaluated with 195 high vaginal swabs referred for antenatal screening and compared with blood agar and Granada medium. The new chromogenic medium showed 100% sensitivity for the detection of Group B streptococci, and also showed a positive predictive value of 100%. Granada medium also showed excellent sensitivity and specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 5 publications
0
8
1
Order By: Relevance
“…We compared i) rectovaginal, vaginal and rectal sampling, and ii) culture on Columbia CNA agar (CNA), on group B streptococcus differential agar (GBSDA) and on Chromogenic Strepto B ID Agar (CA), iii) directly and after Lim broth enrichment. Other groups studying chromogenic agar did so only for vaginal samples [18-20,22], whereas we also included the CDC recommended rectovaginal sampling method, or they did not compare to Granada agar and used miscellaneous samples [23]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We compared i) rectovaginal, vaginal and rectal sampling, and ii) culture on Columbia CNA agar (CNA), on group B streptococcus differential agar (GBSDA) and on Chromogenic Strepto B ID Agar (CA), iii) directly and after Lim broth enrichment. Other groups studying chromogenic agar did so only for vaginal samples [18-20,22], whereas we also included the CDC recommended rectovaginal sampling method, or they did not compare to Granada agar and used miscellaneous samples [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Most other bacterial species are either inhibited or the colonies produced have a different colour (e.g. violet, blue, colourless) [18-20]. …”
Section: Introductionmentioning
confidence: 99%
“…GBS culture in the microbiology laboratory GBS detection by culture was carried out by inoculating in Todd-Hewitt broth supplemented with antibiotics (TODD H-T, BioMérieux, Marcy l'Etoile, France) and then subculture on selective chromogenic agar (ChromID Strepto B Agar, BioMérieux) at 35°C for 24 h [25]. Identification of suspect colonies was further confirmed by a streptococcal agglutination test (Slidex strepto Plus, BioMérieux) to ensure specific identification of GBS.…”
Section: Sample Collectionmentioning
confidence: 99%
“…1). In a study with 134 vaginal swabs Strepto B ID was shown to have a higher specificity and sensitivity than blood agar for detection of S. agalactiae (Perry et al. 2006).…”
Section: Detection Of Streptococcus Agalactiaementioning
confidence: 99%